DISRUPSI EKOSISTEM OTOMOTIF JEPANG DI INDONESIA: ANALISIS STRATEGI SENTRALISASI DAN PENETAPAN HARGA AGRESIF BYDDALAM TRANSISI EV - Ikhsan Maulana; M. Sigit Dwi A, Ovalia (Adisam Publisher, 2025)
For decades, Indonesia's automotive industry has been dominated by a Japanese production ecosystem built upon long-term partnerships between Original Equipment Manufacturers (OEMs) and local suppliers. However, the recent entry of BYD—a Chinese electric vehicle (EV) manufacturer—has disrupted this well-established structure through its centralized supply chain strategy and aggressive pricing. This study aims to analyze the strategic impact of BYD’s business model on the Japanese automotive ecosystem in Indonesia, and to identify the key challenges within the broader context of the country’s EV transition.This research adopts a descriptive qualitative case study approach, utilizing semi-structured interviews with seven informants from Tier 1 and Tier 2 supplier companies serving Japanese OEMs. The data were analyzed using thematic analysis to identify recurring patterns in the experiences and perceptions of industry actors regarding the presence of BYD.Findings reveal that BYD’s centralized approach has weakened the involvement and bargaining power of local suppliers, creating structural tensions within the supply chain. Furthermore, despite offering competitive prices, BYD faces several long-term challenges in Indonesia, including inadequate charging infrastructure, safety concerns related to battery reliability, high total cost of ownership (TCO), and consumer skepticism about product quality. This study contributes to a deeper understanding of industrial disruption in developing countries and provides a foundation for developing adaptive strategies and inclusive industrial policies.